ITC - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The International Trypanotolerance Centre (ITC), established in 1982, conducts research aimed at improving the welfare ofsmall-scale farmers through better livestock production within the mixed farming system. The centre is located in The Gambia...